Pengaruh Marketing Mix 7P terhadap Loyalitas Konsumen dengan Kepuasan Sebagai Mediator di Kopi Bubuk Sinar Baru Cap Bola Dunia - Della, Della; Zebua, Damara Dinda Nirmalasari (Universitas Galuh, 2026)
Sinar Baru Cap Bola Dunia Coffee Powder is one of the oldest traditional coffee brands in Bandar Lampung, currently facing intense market competition. To retain existing customers while attracting new ones, an effective marketing strategy is essential. This study aims to examine the direct and indirect effects of the 7P marketing mix (product, price, place, promotion, people, process, and physical evidence) on consumer loyalty, with satisfaction acting as a mediating variable. The research employed a survey method involving 130 purposively selected respondents. The data were examined using a method called Structural Equation Modeling with Partial Least Squares (SEM-PLS), using SmartPLS 4 software. The results indicate that the 7P marketing mix has a significant and positive direct effect on consumer loyalty (path coefficient = 0.465) and also indirectly affects loyalty through satisfaction as a partial mediator (indirect effect = 0.282). These findings indicate that the direct influence on consumer loyalty is greater than the indirect influence through consumer satisfaction as a mediator. The study provides strategic implications for coffee industry practitioners in designing 7P marketing approaches that are more targeted and consumer-centered.